2012
DOI: 10.1007/s10803-011-1439-y
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Tactile-Perceptual Skill Differences Between Individuals with High-Functioning Autism and Typically Developing Individuals Ages 5–21

Abstract: We examined motor and tactile-perceptual skills in individuals with high-functioning autism (IHFA) and matched typically developing individuals (TDI) ages 5 – 21 years. Grip strength, motor speed and coordination were impaired in IHFA compared to matched TDI, and the differences between groups varied with age. Although tactile-perceptual skills of IHFA were impaired compared to TDI on several measures, impairments were statistically and clinically significant only for stereognosis. Motor and tactile-perceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…To measure touch sensitivity Riquelme et al () used standardised von Frey monofilaments (0.14–1.01 mm) which have documented psychometric properties (Somedic Sales AB, Sweden). To measure tactile perception Abu‐Dahab et al () used the Reitan–Kolve test of Finger Agnosia and Dunn et al (; ) used the standardised Tactile Discrimination Test to measure tactile discrimination. Both measures reported robust psychometric properties for adults (Reitan & Wolfson, ; Carey, Oke, & Matyas, ).…”
Section: Resultsmentioning
confidence: 99%
“…To measure touch sensitivity Riquelme et al () used standardised von Frey monofilaments (0.14–1.01 mm) which have documented psychometric properties (Somedic Sales AB, Sweden). To measure tactile perception Abu‐Dahab et al () used the Reitan–Kolve test of Finger Agnosia and Dunn et al (; ) used the standardised Tactile Discrimination Test to measure tactile discrimination. Both measures reported robust psychometric properties for adults (Reitan & Wolfson, ; Carey, Oke, & Matyas, ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, this increase was significantly more pronounced in children with severe autism as compared with children with mild autism (P = 0.001), and it was not correlated to the severity of the disorder ASD in Arab countries Hussein and Taha 109 aggression. From Jordan, a study reported that motor and tactile-perceptual skills (grip strength, motor speed, and coordination) were impaired in individuals with high-functioning autism when compared with matched normally developing individuals [51]. Also, the rate of pervasive developmental disorders observed in the UAE is comparable to that reported from western countries [12].…”
Section: Egyptmentioning
confidence: 91%
“…Precisely 49 studies comparing ASC and typically-developing (TD) control groups answer this question in the affirmative. The more methodologically rigorous studies, those which a) either matched for chronological and/or mental age and/or IQ or b) controlled for these in their analyses, and c) had more sizeable groups (>30 per group) demonstrate that motor impairments occur more often than might be expected in TD children (AbuDahab, Skidmore, Holm, Rogers, & Minshew, 2013;Ament et al, 2015;Dewey, Cantell, & Crawford, 2007;Dowell, Mahone, & Mostofsky, 2009;Duffield et al, 2013;Dziuk et al, 2007;Floris et al, 2016;Sumner, Leonard, & Hill, 2016;Travers et al, 2015Travers et al, , 2016. A meta-analysis of 41 studies confirmed that, despite substantial variation, effect sizes are large with TD participants significantly outperforming individuals with autism in motor coordination, arm movements, gait and postural stability (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010), and that these effects did not seem affected by publication bias.…”
mentioning
confidence: 99%
“…Other studies of kinematics in very basic arm movements and reaching and grasping reveal differences between autistic and TD participants (Campione, Piazza, Villa, & Molteni, 2016;Cook, Blakemore, & Press, 2013). Use of more traditional neuropsychological tests reflect poorer performance in the grip strength (Abu-Dahab et al, 2013;Hardan et al, 2003;Travers et al, 2015Travers et al, , 2016, finger tapping (Abu-Dahab et al, 2013;Duffield et al, 2013;Hardan et al, 2003;Travers et al, 2016) and pegboard tasks (Abu-Dahab et al, 2013;Ament et al, 2015;Barbeau, Meilleur, Zeffiro, & Mottron, 2015;Duffield et al, 2013;Hardan et al, 2003). These tests ascend in difficulty, primarily testing muscle strength, simple motor coordination and dexterity respectively.…”
mentioning
confidence: 99%